PENINGKATAN KEMAMPUAN MENYAMPAIKAN ISI BERITA DI SURAT KABAR MELALUI METODE BERCERITA SISWA KELAS VI SDN 002 PAGARAN TAPAH DARUSSALAM - Kasmawati Kasmawati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
This research is motivated by the low capabilities delivering news content. Goals to be achieved in this research is to improve the ability of delivering content news newspaper in class VI SDN 002 Pagaran Tapah Darussalam through storytelling method implemented during one month. This research was conducted in SDN 002 Pagaran Tapah Darussalam. Classes that thorough research is a class vi two semesters with a number of students as many as 20 people. This classroom action research was started in early march 2014. This form of research is classroom action research. The research instrument consists of instruments teacher and student activity sheets and achievement test. Based on the research that has been described in chapter IV, it can be concluded that the capacity of students to deliver the news in the newspapers before the action reaches only 55% with the percentage kategeroi "less than optimal" because it is in the range of 40-55%. In the first cycle pupils in the ability to deliver the news in newspapers increased by a percentage of 70% to the category of "enough optimal" because it is in the range of 56-75%. After an improvement of the learning process in the second cycle students' ability to deliver the news in the newspapers has increased very satisfactorily with a percentage of 86% to the category of "optimal" because it is in the range of 76-100%.